Assessment of Thermodynamic Efficiency of the Belarusian Energy System. Part 2 - V. N. Romaniuk; A. A. Bobich; T. V. Ryzhova; T. V. Bubyr; V. V. Yanchuk; Y. S. Yatsukhna (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The energy system is a structure that is among the most complex artificial objects, the successful functioning and development of which is absolutely necessary to ensure the livelihoods of a modern state. In this regard, its continuous monitoring with obtaining reliable and objective performance indicators is undoubtedly in demand. Traditional key energy indicators (specific consumption of conventional fuel for electricity generation and heat release) do not give a complete picture of the operation of the power system for such complex structures and in some cases are calculated incorrectly. The present paper proposes to add a well-known, but practically unused exergetic efficiency coefficient to the range of traditional characteristics. Its application expands the monitoring capabilities and increases the objectivity of the evaluation. For the first time, the analysis of various periods (annual, heating and inter-heating) was carried out on the example of thermal power plants (CHP) of the Unified Energy System of Belarus. The relative power generation of the CHP before the commissioning of the Belarusian NPP was estimated at ≈45 %, and after commissioning it decreased to ≈39 %. More than half of the annual consumption of thermal energy in Belarus is accounted for by heat-generating sources, while thermal power plants provide up to 88 % of heat output. The installed electric capacity utilization factor, the extraction factor and the average annual specific generation of electricity on thermal consumption for each CHP separately have been determined. The results are presented graphically, which makes the content more informative and facilitates the perception. Solutions have been proposed to improve the efficiency of the CHP.